Studi Interaksi Air Tanah Dangkal dan Air Sungai di Sepanjang Daerah Aliran Kali Garang Semarang Menggunakan Isotop Stabil δ18O dan δ2H - Andhihutomo, Rismah Taufik; Satrio, Satrio; Prasetio, Rasi; Wijatna, Agus Budhie (BRIN Publishing, 2017)
A study related to shallow groundwater interaction with Kali Garang River water in Semarang, Central Java using stable isotopes of 18O and 2H has been conducted. As much as 16 groundwater and 3 river water samples were taken for stable isotopes d18O and d2H analysis using Liquid water isotope analyzer LGR DLT-100. The results of analysis shows that there are two area of water recharge origin: the first area contains d18O isotope ranging between -9.41 ‰ to -8.5 ‰ and d2H between -58.2 ‰ to -51.6 ‰; the second area contains isotopes of d18O and d2H -7.15 and -41.55 ‰, respectively. Thus, these results indicate that the first water samples originate from a higher elevation than the origin of the second water sample, but both of them have no interrelation with river water. Whereas, other groundwater samples show that the sample (R4) has interrelation (i.e. mixing) with the river water and two other samples (L1 and R1) have interrelation with salty water or seawater.